Trimethylsilyl Iodide Mediated One‐Pot Synthesis of 2‐Allyl‐2H‐chromenes. Issue 3 (5th December 2014) - Padhi, Birakishore; Reddy, D. Srinivas; Mohapatra, Debendra K.
Abstract: A new and efficient metal‐free trimethylsilyl iodide (TMSI) catalyzed one‐pot synthesis of 2‐allyl‐2 H ‐chromenes has been developed that takes place under mild conditions. The synthesis proceeds through a Wittig reaction by using (triphenylphosphoranylidene)acetaldehyde to form an o ‐hydroxycinnamaldehyde derivative followed by a tandem isomerization and C–O and C–C bond‐forming reactions. The procedure was carried out at room temperature in the presence of 20 mol‐% of TMSI and allyltrimethylsilane in tetrahydrofuran (THF) and provided the 2‐allyl‐2 H ‐chromenes in good to excellent yields. Abstract : A one‐pot metal‐free trimethylsilyl iodide (TMSI) mediated method for the synthesis of 2‐allyl‐2 H ‐chromenes has been developed. The reaction uses commercially available, inexpensive starting materials in a simple procedure that takes place under mild conditions. It is significant that sensitive functional groups on the aromatic ring of the substrate are not affected by the reaction conditions.